SOCIO-PEDAGOGICAL ACTIVITY WITH CHILDREN WHO ARE NOT UNDER THE CARE OF PARENTS - D. Rakhimova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article focuses on the fact that the problem of social orphanhood is a problem typical of most developed and developing nations, the categories of children left without parental care, the causes of orphanhood.